Shear-Dependent Platelet Aggregation: Mechanisms and Therapeutic Opportunities - Rana, Akshita; Westein, Erik; Niego, Be'eri; Hagemeyer, Christoph E. (Frontiers in Cardiovascular Medicine, 2019)
Cardiovascular diseases (CVD) are the number one cause of morbidity and death worldwide. As estimated by the WHO, the global death rate from CVD is 31% wherein, a staggering 85% results from stroke and myocardial infarction. Platelets, one of the key components of thrombi, have been well investigated over decades for their pivotal role in thrombus development in healthy as well as diseased blood vessels. In hemostasis, when a vascular injury occurs, circulating platelets are arrested at the site of damage, where they are activated and aggregate to form hemostatic thrombi, thus preventing further bleeding. However, in thrombosis, pathological activation of platelets occurs, leading to uncontrolled growth of a thrombus, which in turn can occlude the blood vessel or embolize, causing downstream ischemic events. The molecular processes causing pathological thrombus development are in large similar to the processes controlling physiological thrombus formation. The biggest challenge of anti-thrombotics and anti-platelet therapeutics has been to decouple the pathological platelet response from the physiological one. Currently, marketed anti-platelet drugs are associated with major bleeding complications for this exact reason; they are not effective in targeting pathological thrombi without interfering with normal hemostasis. Recent studies have emphasized the importance of shear forces generated from blood flow, that primarily drive platelet activation and aggregation in thrombosis. Local shear stresses in obstructed blood vessels can be higher by up to two orders of magnitude as compared to healthy vessels. Leveraging abnormal shear forces in the thrombus microenvironment may allow to differentiate between thrombosis and hemostasis and develop shear-selective anti-platelet therapies. In this review, we discuss the influence of shear forces on thrombosis and the underlying mechanisms of shear-induced platelet activation. Later, we summarize the therapeutic approaches to target shear-sensitive platelet activation and pathological thrombus growth, with a particular focus on the shear-sensitive protein von Willebrand Factor (VWF). Inhibition of shear-specific platelet aggregation and targeted drug delivery may prove to be much safer and efficacious approaches over current state-of-the-art antithrombotic drugs in the treatment of cardiovascular diseases.